Cipo y la monarquía en Metamorfosis de Ovidio - Mollo Brisco, María Eugenia (Centro de Estudios Latinos. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2017)
Our purpose in this paper is to analyse how the Cipus episode in Ovid's Metamorphoses XV gives a literary shape to a crisis of experience: the end of the Republic and the transition to a new form of government, the Principate. We will take as a theoretical framework Raymond Williams ´s concept of "structure of feeling", which is defined as the expression of the interaction between the dominant social character of a period and actual experience. We postulate that the Cipus episode points to a conflict between a dominant idea, the negative view over the king ´s figure, and a new feeling, the possibility of a virtuous king.